Implementasi Manajemen Berbasis Madrasah - Fitriani Fitriani (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
School/madrasah-based management is a management model that gives schools/madrasah greater autonomy and encourages direct participation of school members and the community to improve school quality based on national education policies, laws and regulations. MBS implementation strategies may differ between countries and regions. In fact, schools in the same area may have different strategies. The components of school/madrasah-based management are management of educators and education personnel, financial management of education, management of facilities and infrastructure and management of school and community relations.